Karakteristik Belajar dan Language Anxiety dalam Pembelajaran Bahasa Arab: Analisis Konseptual dan Implikasi Paedagogis - Octavia Putri Purnama Syari; Johan Rafaro; Ikfina Himmatus Saadah; M Yunus Abu Bakar (Moral : Jurnal kajian Pendidikan Islam, 2026)
Arabic language learning is influenced not only by cognitive ability but also by students’ learning characteristics, including affective, social, and physiological dimensions, particularly the phenomenon of language anxiety that often hinders language performance. This study aims to analyze the relationship between students’ learning characteristics and the emergence of language anxiety in Arabic language learning, as well as to formulate its implications for instructional strategies. This research employs a qualitative approach through a conceptual study based on relevant literature concerning learning characteristics and language anxiety. The findings indicate that variations in students’ characteristics contribute to different levels of anxiety across the four language skills: listening, speaking, reading, and writing. Language anxiety is multidimensional and affects students’ participation, motivation, and academic performance. Therefore, Arabic language instruction should be designed using differentiated, communicative, and student-centered approaches while fostering a supportive learning environment. The study highlights the importance of the teacher’s role as a facilitator who understands students’ cognitive and affective dynamics in order to create more effective, humanistic, and responsive Arabic language learning.